Performance Analysis of Horizontal Axis Wind Turbine using Variable Blade Pitch Control Mechanism - Shuwa, M.; Ngala, G. M.; El- jummah, A. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This work investigates the performance of a horizontal axis wind turbine (HAWT) with variable blade pitch control mechanism. The control mechanism is a simple mechanical Watt governor design, which was developed to regulate the blade pitch angle of the HAWT depending on wind speed magnitude. The HAWT model with the control mechanism was tested for performance in a wind tunnel. Response of the control mechanism in terms of blade pitch angle, rotor speed and generator power output were analyzed based on regulated predetermined wind speeds. The result shows a gradual increase in rotor speed and a proportional increase in generator power output between cut-in wind speed of 2.5m/s and rated wind speed of 6 m/s. These parameters were kept constant at 100 RPM and 50 Watts as observed due to the steady response of the control mechanism. The steadiness lasted up to a cut-out wind speed of 9 m/s. The control mechanism subsequently shutdown the turbine at the cut-out wind speed to protect the turbine against wind speeds higher than 9 m/s. The performance test predicts that the variable blade pitch control mechanism was able to regulate and bring about the require control of HAWT model. The mechanism allows the turbine to only operate between 2.5 and 9 m/s at blade pitch angle between 82 and 90 degrees from the axis of wind flow and change in governor height between 0 to 8 mm.